2016
DOI: 10.1519/jsc.0000000000001292
|View full text |Cite
|
Sign up to set email alerts
|

Tapering Practices of New Zealand's Elite Raw Powerlifters

Abstract: The major aim of this study was to determine tapering strategies of elite powerlifters. Eleven New Zealand powerlifters (28.4 ± 7.0 years, best Wilks score of 431.9 ± 43.9 points) classified as elite were interviewed, using semi-structured interviews, about their tapering strategies. Interviews were transcribed verbatim and content analyzed. Total training volume peaked 5.2 ± 1.7 weeks from competition while average training

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(102 citation statements)
references
References 28 publications
20
82
0
Order By: Relevance
“…These results (1,31,32) are somewhat consistent with the findings of Pritchard et al (25) who reported that elite powerlifters usually take 3.7 ± 1.6 days off prior to important competitions.…”
Section: A C C E P T E Dsupporting
confidence: 91%
“…These results (1,31,32) are somewhat consistent with the findings of Pritchard et al (25) who reported that elite powerlifters usually take 3.7 ± 1.6 days off prior to important competitions.…”
Section: A C C E P T E Dsupporting
confidence: 91%
“…The heavy taper had significantly greater percentage increases in leg press 1RM and isometric peak force than the light taper. These findings are similar to qualitative findings showing elite powerlifters usually maintain a high intensity of training when peaking for important events while significantly reducing volume (>50%) 10,14 . However, Zaras et al 8 did not control training volume in each taper, and therefore their reported enhancement of strength performance may be due to a combination of changes in training volume and intensity, not solely intensity.…”
Section: Introductionsupporting
confidence: 87%
“…Complete training cessation has been shown to be beneficial for maximal strength performance when undertaken for short periods of time (up to a week) in several studies 17,26,27 . Both qualitative studies 10,14 noted that powerlifters take training cessations of 3.7 ± 1.6 days and 3 ± 1 days, respectively, to finish the taper. These results again emphasise that short term training cessation (or complete volume reduction) is an important part of the strength taper.…”
Section: Discussionmentioning
confidence: 99%
“…Strongman athletes completed a self-reported 4-page retrospective Tapering Practices of Strongman Athletes Survey created for this study, which was based on interview questions used with powerlifters [ 23 , 24 ]. The original Strongman Tapering Practices Survey was pilot tested with university professors and strongman athletes to ensure its ease of use with this population.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the reliability of the Internet assessment method for use with strength athletes, including the strongman population, is currently lacking. The Tapering Practices of Strongman Athletes survey created for this study was based on nine interview questions used with powerlifters [ 23 , 24 ]. Our tapering practice questionnaire has included the addition of several questions, as well as changes to the wording of original questions used in previous studies [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%